A new term Jzeff derived from measured total attenuation coefficients of photons near the absorption edges of some compounds - Polat, Recep; Icelli, Orhan (ELSEVIER SCIENCE BV, 2010)
In order to determine the effect of XAFS (X-ray absorption fine structure) on J(zeff) we have measured mu/p values of compounds, which are determined by the mixture rule or the independent atomic model. Also, we want to obtain both XAFS effect and non-applicability or applicability of mixture rule. The most crucial finding in this study is that measurement of the effective atomic number is not appropriate near the absorption edge and the effective atomic number is affected by near the absorption edge. The results obtained have been compared with theoretical values. Also, the objective of this study is to show that there is a term J(zeff) between effective atomic numbers and absorption jump factor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Mass attenuation coefficients; Molecular; Atomic cross-sections; Effective atomic number; Jump ratio; Jump factor; EFFECTIVE ATOMIC NUMBERS; BIOLOGICALLY IMPORTANT COMPOUNDS; ESSENTIAL AMINO-ACIDS; X-RAY-ABSORPTION; RANGE 1 KEV; CROSS-SECTIONS; TRANSMISSION EXPERIMENTS; SHIELDING MATERIALS; ELECTRON-DENSITIES; ENERGY-ABSORPTION; Instruments & Instrumentation; Nuclear Science & Technology; Physics